Fatal Landslide Database of Turkey (FATALDOT) - Gorum, Tolga; Fidan, Seckin (Copernicus GmbH, 2020)
Landslides are one of the destructive geomorphological hazards that cause substantial socio-economic and environmental damages on a global scale. Knowing the precise number of deaths caused by landslides and their spatial and temporal distributions will facilitate a better understanding of the losses and damages, and further to prevent and minimize the damages caused by this type of disasters. Thus, reliable historical inventories, including past landslide events, are crucial in understanding the future landslide hazards and risks. Turkey, similar to mountainous countries suffering from landslides, is also high-elevated (average altitude of >1100 m) and tectonically active country located where the Europe and Asia continents meet. In the years between 1995-2014, 335 of the total 1375 fatalities caused by landslides in European countries have occurred in Turkey. This reported number not only shows that Turkey is the first country in Europe in terms of deaths caused by landslides but also implies that the landslide related problems are overwhelming than expected in Turkey. Although many studies have been carried out on individual landslides and landslide inventories in Turkey, we have limited information about the landslides that cause death. However, there are many landslide events that resulted in the deaths of tens of people every year in Turkey. Therefore, neglecting fatal landslides and their consequences resulted in an unrealistic comprehension of landslide risk. In this respect, we contribute to filling this data gap by presenting the first country-scale archive inventory of fatal landslides, their spatio-temporal distribution, and the triggering mechanism characteristics for Turkey, which is Europe's topmost deadly country. The fatal landslide events in Turkey for the period from 1929 to 2019 were compiled from various sources comprising national and local printed and digital media reports with pre-determined keywords in Turkish, academic papers, disaster, and city annual reports, and government and aid agency reports. According to the new database, 1343 people lost their lives as a result of 389 landslide events in Turkey between 1929 and 2018. In total 197 fatal landslide events, which resulted in 301 deaths, were identified due to anthropogenic triggers (i.e., construction, infrastructure, and mining activities). On the other hand, 147 landslides occurred, and 883 people lost their lives due to natural triggering factors. The natural trigger origin of the fatal landslides is concentrated in the Eastern Black Sea and is generally shallow landslides corresponding to regolithic zones where chemical weathering is severe. On the contrary, the trigger factor of 45 landslide events cannot be assigned to the FATALDOT database due to a lack of detailed information in incidence reports. The database, which is planned to be transformed into an information system with a semi-automatic update feature, is thought to be an underlying data source for future research works to prevent hazard and risk studies and landslide-related deaths in the country scale.